Pengembangan Lembar Kerja Peserta Didik (LKPD) dengan Model Discovery Learning Berbasis Augmented Reality pada Materi Ikatan Kimia untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Ade Kurnia Putri Tanjung; Isana Supiah Yosephine Louise (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to: (1) produce student worksheets with an augmented reality-based discovery learning model on chemical bond material that is appropriate for increasing student motivation and learning outcomes; (2) determine the effectiveness of Student Worksheets with augmented reality-based discovery learning models on chemical bond material in increasing student motivation and learning outcomes. This development research uses a 4D development model including the Define, Design, Development and Disseminate stages. The trial was carried out on Grade X Science students at SMA Sejahtera 1 Depok with a quasi-experimental design, nonequivalent control group design model. The research instruments used were validation sheets, learning motivation questionnaires and learning outcomes questions. The research results show that: (1) student worksheets with augmented reality based discovery learning model on chemical bonding material that has been developed has very decent quality, which can be proven by the results of the average validation value by material experts of 3.926, media experts of 3.969 and student responses of 3.93; (2) student worksheets with a discovery learning model based on augmented reality is effective in increasing student motivation and learning outcomes with the MANOVA test which obtained a significance value of 0.000 and had an effective contribution of 23.3%.